Literacy, Teens, Refugees, and Soccer - Dwyer, Eric; McCloskey, Mary Lou (Refuge: Canada's Journal on Refugees, 2013)
This study examined the literacy development of teenage refugee boys in a one-month intensive summer literacy camp. The study intervention sought to abate literacy regression among language minority students in a suburban southern US city by combining physical training and promotion of literacy culture. Students experienced an intensive schedule of athletics and reading/writing workshops. Data were collected regarding student writing, reading proficiency, and dispositions toward literacy practices. Outcomes included increased expressed student enjoyment expressed for both reading and writing, especially for the experience of older students reading to younger peers. In addition, data indicated that summer literacy regression was largely avoided. However, reading proficiency level assessments foreshadow obstacles for students in achieving timely high school graduation. Finally, means used by mainstream teachers of assessing the literacy of refugee students, especially compared to assessments of proficient English-speaking students, are critiqued.